The effects of changing chemistry on the shock response of basic polymers - Millett, Jeremy C. F.; Brown, Eric N.; Gray III, George T.; Bourne, Neil K.; Wood, David C.; Appleby-Thomas, Gareth J. (Springer, 2016)
The shock response of four common semicrystalline thermoplastic polymers—polyethylene (PE), polyvinylchloride (PVC), polytetrafluoroethylene (PTFE) and polychlorotrifluoroethylene (PCTFE)—have been studied in terms of their Hugoniots, release velocities and shear strengths. Through the variations in behaviour caused by changes to the attached atoms to the carbon backbone, it has been possible to suggest that there are two main factors in play. The first is an electrostatic repulsion between adjacent polymer chains. Where this force is large, for example in PTFE with highly electronegative fluorine atoms, this results in this force dominating the shock response, with low shock velocities, high release velocities and little if no hardening behind the shock front. In contrast, in materials such as PE, this force is now weaker, due to the lower electronegativity of hydrogen, and hence this force is easier to overcome by the applied shock stress. Now the main factor affecting shock behaviour is controlled by the shape of the polymer chain allowing inter chain tangling (tacticity). This results in higher shock velocities, lower release speeds and significant hardening behind the shock front as the chains are forced together. This is prevalent in materials with a relatively open structure such as PE and is enhanced with the presence of large side groups or atoms off the main polymer chain.
Keywords: Polyethylene; Polyvinylchloride; Polytetrafluoroethylene; Polychlorotrifluoroethylene; Shock